THE INFLUENCE OF LEADERSHIP STYLE ON SERVICE QUALITY IN HIGHER EDUCATION: A STUDY AT A SOCIAL SCIENCE FACULTY - Wijaya, Andy Fefta; Prastyari, Catrine Ana; Armanu, Armanu (Jurnal Aplikasi Manajemen, 2019)
This study aimed at disclosing the influence of the leadership style on the service quality in Higher Education Institution. This study population is 103 supporting staffs of a social science faculty, with a proportional random sampling of 80 people. The hypothesis in this study was analyzed by using the structural model of Partial Least Square.Based on the results of Partial Least Square testing, it is disclosed that there is a significant influence of the leadership style on the service quality at the faculty being studied. The positive correlation shows that the stronger the leadership style is, the higher the leadership style impact on the service quality will be.